The Comparative Study of Form and the Structure of Sri Lankan Gaá¹aberÄ and Pahatharaá¹a BerÄ with the Indian Mridanga Drum - Dehideniya, Isuru (Talenta Publisher, 2021)
The Gaá¹aberÄ and Pahataraá¹a berÄ are the main drums in two regions in Sri Lanka; also the Mridanga is one of all South Indian main drums. This research is a comparative analysis of the similarities and differences of form and structure between those Indians and Sri Lankans drums. That is conducted in the qualitative method. Several similarities and differences are discovered from the form and structure between those drums under the organization, order of the elements, construct process, and shape. The final conclusions are, 1) the form of all drum heads of Gatabera, Pahatharata bera, and Mridanga is similar, and also that form represents an Indian subcontinent drum head variety, but their structure is different according to the culture of both countries. 2) The form and structure of Gatabera and Mridanga drum bodies are slightly similar.